The Palgrave Handbook of Global Counterterrorism Policy 2017
DOI: 10.1057/978-1-137-55769-8_49
|View full text |Cite
|
Sign up to set email alerts
|

When Diplomacy Identifies Terrorism: Subjects, Identity and Agency in the ‘War on Terror’ in Mali

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Diplomatic missions also play a key role in conflict prevention and mediation, by allowing third parties to help resolve local bargaining disagreements between two or more warring parties (Ruhe, 2020). Embassies and consulates are likewise important in helping to identify and prevent terrorism, promoting security and stability not only in their sending country, but also-by allowing local and international authorities to target terrorist groups-locally in the host state (de Orellana, 2017). By reducing diplomatic activities, malaria may therefore subject some nation-states to a higher risk of military, political, and human insecurity (Cervellati et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Diplomatic missions also play a key role in conflict prevention and mediation, by allowing third parties to help resolve local bargaining disagreements between two or more warring parties (Ruhe, 2020). Embassies and consulates are likewise important in helping to identify and prevent terrorism, promoting security and stability not only in their sending country, but also-by allowing local and international authorities to target terrorist groups-locally in the host state (de Orellana, 2017). By reducing diplomatic activities, malaria may therefore subject some nation-states to a higher risk of military, political, and human insecurity (Cervellati et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam 1945–1948, it was demonstrated that racial representations of subjects and their spatial (Oriental), temporal (backward) and normative (red conspiracy) contexts have immense power in diplomacy. Application of this method to US diplomacy with Mali and Morocco in the 2000s showed that representation of the Self as a postcolonial subaltern was empowering for these North African states, allowing them to significantly influence US policy (de Orellana, 2015, 2016). This understanding of what enables crossovers paves the way for future conceptualisation and empirical examination of the agency that enables diplomacy to transform how other actors see the world.…”
Section: Conclusion: Accounting For the Power Of Diplomatic Text And mentioning
confidence: 99%